Redistribution does matter: Growth and redistribution for poverty reduction - Hulya Dagdeviren; Rolph vander Hoeven; John Weeks (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Recent development literature has placed priority on poverty reduction, and on possible growth enhancement from a more equal distribution of assets and income. At the same time, empirical work consistently shows that economic growth is no more than distribution neutral. In that context, this paper explores the relationship among growth, inequality and poverty, and demonstrates the following general conclusions: 1) a redistributive growth path is always likely to be superior to a distribution neutral path (`trickle down') for reducing poverty; 2) a redistributive growth path is always superior if a country's per capita income and inequality are relatively high; and 3) a static redistribution from the rich to the poor is superior to a redistributive growth path in its effect on poverty for most countries, but not for all. The paper then considers policy that might be used to make growth more equitable. – poverty ; inequality ; growth ; redistribution
Keywords: D30; D31; H2; H5; I32; 330; Einkommensverteilung; Armut; Armutspolitik; Einkommensumverteilung; Wirtschaftswachstum; Welt